Positive electrode active material and preparation method, positive electrode sheet, battery, and application
By introducing the Keggin structure of ammonium phosphomolybdate and manganese doping in lithium iron phosphate and using carbon cladding, the problem of poor rate performance of lithium iron phosphate is solved, and the high cycle stability and rate performance of the battery are improved. .
Patent Information
- Application Number
- CN202411433124.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-10
- Estimated Expiration
- 2044-10-15
AI Technical Summary
As a positive electrode active material, lithium iron phosphate limits its application field due to its poor rate performance, and existing doping methods cannot effectively improve the performance of the battery.
Manganese-doped lithium iron phosphate was modified with ammonium phosphomolybdate with Keggin structure, and the conductivity was improved by carbon coating to prepare a positive electrode active material with excellent cycle stability and rate performance.
It significantly improves the cycle stability and rate performance of the battery, improves the thermal stability and conductivity of the battery, and extends the cycle life of the battery.
Smart Images

Figure CN118943348B_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of preparation of lithium-ion batteries, and specifically to a positive electrode active material and a preparation method, a positive electrode sheet, a battery, and applications. Background Art
[0002] Lithium iron phosphate (LiFePO4) is used as a positive electrode active material because of its high thermal stability and long cycle life, but its application areas are limited due to its defects such as low rate performance.
[0003] Currently, by doping lithium iron phosphate with metals (such as manganese, cobalt, nickel, aluminum, titanium, etc.) or non-metals (such as nitrogen, sulfur, fluorine, etc.), the conductivity and ion diffusion coefficient of lithium iron phosphate can be effectively improved, thereby improving the rate performance of the battery. However, due to the limitations of the lithium iron phosphate structure itself, the improved battery performance cannot meet the demand. Summary of the invention
[0004] In order to solve the above problems, the present application proposes a positive electrode active material and preparation method, a positive electrode sheet, a battery, and an application. In the positive electrode active material, ammonium phosphomolybdate with a Keggin structure is used to modify manganese-doped lithium iron phosphate, which effectively improves the cycle stability and rate performance of the battery; the carbon coating layer improves the conductivity of the positive electrode active material.
[0005] This application is implemented through the following technical solutions:
[0006] In a first aspect, the present application provides a positive electrode active material, including ammonium phosphomolybdate, manganese-doped lithium iron phosphate and a carbon coating layer;
[0007] The ammonium phosphomolybdate modified manganese doped lithium iron phosphate;
[0008] The carbon coating layer coats ammonium phosphomolybdate-modified manganese-doped lithium iron phosphate.
[0009] In some possible implementations, in the manganese-doped lithium iron phosphate, the molar ratio of manganese to lithium iron phosphate is (0.005-0.05):1.
[0010] In some possible implementations, the molar ratio of the manganese-doped lithium iron phosphate to the ammonium phosphomolybdate is 5:(0.01-0.02).
[0011] In some possible implementations, the carbon coating layer is at least one layer, and the thickness of the single carbon coating layer is 10 nm to 30 nm.
[0012] In some possible implementations, the tap density of the positive electrode active material is 0.7 g / cm 3 ~1.5g / cm 3 .
[0013] In a second aspect, the present application proposes a method for preparing a positive electrode active material, comprising the following steps:
[0014] Adding phosphoric acid solution to the mixed suspension for mixed reaction to obtain a precursor; wherein the components in the mixed suspension include manganese-doped lithium iron phosphate and ammonium molybdate;
[0015] The precursor is dried, washed, spray-dried, and then carbon-coated to obtain a positive electrode active material.
[0016] In some possible implementations, the mixing reaction comprises the steps of:
[0017] At a temperature of 60° C. to 90° C., adding a phosphoric acid solution to the mixed suspension and stirring for reaction for 1 h to 3 h to obtain a reaction solution;
[0018] The pH value of the reaction solution is adjusted by a pH adjuster to obtain a precursor with a pH value of 3 to 5.
[0019] In some possible implementations, the molar ratio of the lithium iron phosphate, the ammonium molybdate and the phosphoric acid in the manganese-doped lithium iron phosphate is 5:(0.12-0.2):(0.02-0.03).
[0020] In some possible implementations, the drying temperature is 100° C. to 150° C., and the drying time is 0.5 h to 3 h.
[0021] In some possible implementations, the spray drying includes pressure spray drying, in which the inlet air temperature is 200° C. to 300° C., the outlet air temperature is 95° C. to 100° C., and the inlet air pressure is 0.2 MPa to 0.6 MPa.
[0022] In a third aspect, the present application proposes a positive electrode plate, wherein the positive electrode plate includes the positive electrode active material described in the present application or the positive electrode active material prepared by the preparation method described in the present application.
[0023] In a fourth aspect, the present application provides a battery, comprising a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte;
[0024] The positive electrode plate includes the positive electrode plate described in the present application.
[0025] In the fifth aspect, the present application proposes an application of the positive electrode active material described in the present application, the positive electrode active material prepared by the preparation method of the positive electrode active material described in the present application, the positive electrode plate described in the present application, or the battery described in the present application in household appliances, electric vehicles, electric cars, electric trains, ships, satellites or energy storage systems.
[0026] Compared with the prior art, the positive electrode active material and preparation method, positive electrode sheet, battery, and application provided in this application have at least the following beneficial technical effects:
[0027] (1) In the positive electrode active material of the present application, the molybdenum element can improve the conductivity of the positive electrode active material and enhance the cycle performance of the positive electrode active material; the manganese element can effectively improve the conductivity of the positive electrode active material, thereby improving the discharge performance and cycle life of the battery and improving the thermal stability of the battery; the ammonium phosphomolybdate has a Keggin cage structure with high symmetry and stability. In the manganese-doped lithium iron phosphate modified with ammonium phosphomolybdate, lithium ions are located in the gaps of the crystal structure and are easy to embed and remove, thereby effectively improving the cycle stability and rate performance of the battery; the carbon coating layer not only improves the conductivity of the positive electrode active material, but also protects the material coated therein.
[0028] (2) The preparation method of the positive electrode active material of the present application comprises the following steps: in a mixing reaction, ammonium molybdate and phosphoric acid are in situ generated into ammonium phosphomolybdate with a Keggin structure, which is used to modify manganese-doped lithium iron phosphate to obtain a precursor; the precursor is dried to remove moisture, excess phosphoric acid and ammonium phosphate are removed by washing, and a carbon coating layer is coated after spray granulation to obtain a positive electrode active material of manganese-doped lithium iron phosphate modified with a Keggin structure; the prepared positive electrode active material has excellent conductivity, cycle stability and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present drawings or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present drawings. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying any creative work.
[0030] Figure 1 A schematic diagram of a process for preparing a positive electrode active material in an embodiment of the present application;
[0031] Figure 2 This is a SEM image of the positive electrode active material in Example 1 of the present application.
[0032] The purpose, features and advantages of this figure will be further described in conjunction with the embodiments with reference to the accompanying drawings. DETAILED DESCRIPTION
[0033] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0034] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0035] In this application, "at least one" means one or more, and "more than one" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, a~b (i.e. a and b), a~c, b~c, or a~b~c, where a, b, c can be single or multiple, respectively.
[0036] The terms "first" and "second" are used only for descriptive purposes to distinguish objects such as substances from each other, and should not be understood as indicating or implying relative importance or implicitly indicating the number of technical features indicated. For example, without departing from the scope of the implementation regulations of this application, the first XX can also be called the second XX, and similarly, the second XX can also be called the first XX. Therefore, the features defined as "first" and "second" can explicitly or implicitly include one or more of the features.
[0037] The terms used in the embodiments of the present application are only for the purpose of describing specific implementation rules, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the implementation rules of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0038] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the implementation regulations of this application.
[0039] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0040] Unless otherwise defined, all professional terms used below have the same meanings as those generally understood by those skilled in the art. The professional terms used herein are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention.
[0041] Unless otherwise specified, various raw materials, reagents, instruments and equipment used in this application can be purchased from the market or prepared by existing methods.
[0042] The chemical formula of the term "ammonium phosphomolybdate" is (NH4)3PMo 12 O 40 (molar mass is about 1876.37 g / mol), which is a typical Keggin structure.
[0043] Traditional lithium iron phosphate materials are widely used due to their high safety, stability, environmental friendliness and low production cost. However, due to its poor rate performance and low energy density, it must be modified and upgraded in order to further expand the market. Although lithium iron phosphate can be doped with metal elements (such as manganese, cobalt, nickel, aluminum, titanium, etc.) and / or non-metals (such as nitrogen, sulfur, phosphorus, fluorine, etc.), due to the limitations of the lithium iron phosphate structure (olivine structure) itself, the effect of the doped metal elements on the rate performance and energy density of lithium iron phosphate is limited.
[0044] The Keggin structure is a typical polyoxometalate (POM) structure, which is a basic structural unit consisting of a central atom (usually P, Si, Ge, etc.) and four auxiliary atoms (such as Mo, W, V, Nb, etc.) surrounding a tetrahedral center. This structure consists of 12 connected five-membered rings and has high stability and reactivity. The Keggin structure is used in the field of catalysts because of its excellent thermal stability, chemical stability and structural diversity, but in the field of battery materials, the Keggin structure has failed to exert its electrical properties. And due to the difference in electrochemical properties between the Keggin structure and lithium iron phosphate, a technical bias has been formed.
[0045] In order to effectively exert the electrical properties of the Keggin structure and improve the rate performance and capacity density of lithium iron phosphate materials, the embodiments of the present application propose a positive electrode active material and preparation method, a positive electrode plate, a battery, and an application. In the positive electrode active material, ammonium phosphomolybdate with a Keggin structure is modified to form manganese-doped lithium iron phosphate, which can effectively improve the cycle stability, rate performance and capacity density of the battery; the carbon coating layer improves the conductivity of the positive electrode active material. The preparation method adopts an in-situ synthesis method to make ammonium molybdate and phosphoric acid in situ to generate ammonium phosphomolybdate to modify manganese-doped lithium iron phosphate, so that the crystal structure of ammonium phosphomolybdate modified manganese-doped lithium iron phosphate is more stable, thereby effectively improving the cycle stability, rate performance and capacity density of the battery.
[0046] The following is a detailed description of a positive electrode active material and a preparation method, a positive electrode sheet, and a battery in an embodiment of the present application.
[0047]
Positive electrode active material
[0048] In a first aspect, an embodiment of the present application provides a positive electrode active material, including ammonium phosphomolybdate, manganese-doped lithium iron phosphate and a carbon coating layer;
[0049] Ammonium phosphomolybdate modified manganese-doped lithium iron phosphate;
[0050] The carbon coating layer is coated with ammonium phosphomolybdate-modified manganese-doped lithium iron phosphate.
[0051] In the positive electrode active materials of the embodiments of the present application, molybdenum can improve the conductivity of the positive electrode active materials and enhance the cycle performance of the positive electrode active materials; manganese can effectively improve the conductivity of the positive electrode active materials, thereby improving the discharge performance and cycle life of the battery, and improving the thermal stability of the battery; the carbon coating not only improves the conductivity of the positive electrode active materials, but also protects the materials coated therein. In the positive electrode active materials, ammonium phosphomolybdate has a Keggin cage structure with high symmetry and stability. In the manganese-doped lithium iron phosphate modified with ammonium phosphomolybdate, the lithium ions are located in the gaps of the crystal structure and are easy to embed and remove. Ammonium phosphomolybdate modified manganese-doped lithium iron phosphate can effectively improve the cycle stability and rate performance of the battery; the carbon coating layer improves the conductivity of the positive electrode active materials.
[0052] In some embodiments, in the manganese-doped lithium iron phosphate, the molar ratio of manganese to lithium iron phosphate is (0.005~0.05):1. In the exemplary embodiment, it can be a typical but non-limiting mass ratio such as 0.005:1, 0.01:1, 0.03:1, 0.05:1, or a range between any two mass ratios. In some embodiments, the average particle size Dv50 of the manganese-doped lithium iron phosphate is 1μm~5μm. In the exemplary embodiment, it can be a typical but non-limiting average particle size such as 1μm, 2.5μm, 5μm, or a range between any two average particle sizes. In this case, ammonium phosphomolybdate is easy to modify the manganese-doped lithium iron phosphate, and the modified manganese-doped lithium iron phosphate has excellent electrical properties.
[0053] In some embodiments, the molar ratio of manganese-doped lithium iron phosphate to ammonium phosphomolybdate is 5:(0.01-0.02). In exemplary embodiments, the molar ratio may be 5:0.01, 5:0.016, 5:0.02, or any range between any two molar ratios.
[0054] In some embodiments, the carbon coating layer is at least one layer, and the thickness of the single carbon coating layer is 10nm~30nm. In the exemplary embodiment, it can be a typical but non-limiting thickness such as 10nm, 15nm, 20nm, 25nm, 30nm, or a range between any two thicknesses.
[0055] In some embodiments, the tap density of the positive electrode active material is 0.7 g / cm 3 ~1.5g / cm 3 In the example, it can be 0.7 g / cm 3 , 0.9g / cm 3 , 1.0g / cm 3 , 1.5g / cm 3 Typical but non-limiting tap density or a range between any two tap densities. Within this tap density range, the energy density of the battery is effectively increased.
[0056] [A method for preparing a positive electrode active material]
[0057] The second aspect of the present application provides a method for preparing a positive electrode active material, such as Figure 1 As shown, the following steps are included:
[0058] S10. Adding phosphoric acid solution to the mixed suspension for mixing reaction to obtain a precursor; wherein the components in the mixed suspension include manganese-doped lithium iron phosphate and ammonium molybdate.
[0059] S20. After drying the precursor, washing, spray drying, and then carbon coating are performed to obtain a positive electrode active material.
[0060] In the preparation method of the positive electrode active material of the embodiment of the present application, in a mixing reaction, ammonium molybdate and phosphoric acid in situ generate ammonium phosphomolybdate with a Keggin structure, which is used to modify manganese-doped lithium iron phosphate to obtain a precursor; the precursor is then dried to remove moisture, and excess impurities such as phosphoric acid and ammonium phosphate are removed by washing. After spray granulation, a carbon coating layer is coated to obtain a positive electrode active material of manganese-doped lithium iron phosphate modified with a Keggin structure; the prepared positive electrode active material has excellent conductivity, cycle stability and rate performance.
[0061] [Step S10]
[0062] In some embodiments, in the above step S10, the average particle size Dv50 of the manganese-doped lithium iron phosphate is 1 μm to 5 μm. In the exemplary embodiment, it can be a typical but non-limiting average particle size such as 1 μm, 2.5 μm, 5 μm, or a range between any two average particle sizes. The manganese-doped lithium iron phosphate can be selected from existing commercially available materials or can be prepared as long as the required average particle size and molar ratio of manganese to lithium iron phosphate are met.
[0063] In some embodiments, in the above step S10, the preparation of the mixed suspension includes the steps of: mixing ammonium molybdate and a solvent in a preset ratio to obtain an ammonium molybdate solution, and then dispersing manganese-doped lithium iron phosphate in the ammonium molybdate solution to obtain a mixed suspension.
[0064] In some embodiments, the solvent includes at least one of water, methanol, ethanol, and acetone.
[0065] In some embodiments, the mass fraction of ammonium molybdate in the ammonium molybdate solution is 10% to 28%. In exemplary embodiments, it can be a typical but non-limiting mass fraction such as 10%, 15%, 28%, or a range between any two mass fractions.
[0066] In some embodiments, in the above step S10, the mixed suspension further includes a surfactant. The surfactant can promote the uniform dispersion of manganese-doped lithium iron phosphate in the mixed suspension. The material of the surfactant can be any material that meets the requirements, and is not required, but as an example, the surfactant can be sodium dodecylbenzene sulfonate (SDBS), hexadecyltrimethylammonium bromide (CTAB), etc.
[0067] In some embodiments, in the above step S10, the mixing reaction comprises the steps of:
[0068] S11. Add the phosphoric acid solution to the mixed suspension at a temperature of 60°C to 90°C and stir to react for 1h to 3h to obtain a reaction solution.
[0069] S12. Use a pH adjuster to adjust the pH value of the reaction solution to obtain a precursor with a pH value of 3 to 5.
[0070] In the above-mentioned mixing reaction step, reacting at a temperature of 60° C. to 90° C. and stirring can form ammonium phosphomolybdate having a Keggin structure; adjusting the pH value of the solution to acidity can make the formed Keggin structure more stable and modify the manganese-doped lithium iron phosphate.
[0071] In some specific embodiments, in the above step S11, the stirring speed during the stirring reaction is 100rpm~200rpm, and in the exemplary example, it can be a typical but non-limiting stirring speed such as 100rpm, 150rpm, 200rpm, or a range between any two stirring speeds. In some specific embodiments, in the above step S11, when phosphoric acid is added to the mixed suspension, the speed of addition is 20d / min~40d / min, and in the exemplary example, it can be a typical but non-limiting speed such as 20d / min, 25d / min, 30d / min, 35d / min, 40d / min, or a range between any two speeds. In this speed range, combined with the stirring speed, it is possible to avoid precipitation caused by excessive local concentration.
[0072] In some specific embodiments, in the above step S12, the pH adjusting agent includes one or more of concentrated ammonia water, ammonium nitrate, and dilute nitric acid. In this case, the selection of ammonia water, ammonium nitrate, etc. will not introduce new impurities.
[0073] In some specific embodiments, the concentration of dilute nitric acid is 3% to 30%. In exemplary embodiments, it can be 3%, 8%, 10%, 20%, 30%, or other typical but non-limiting mass fractions or a range between any two mass fractions.
[0074] In some embodiments, in the above step S10, the molar ratio of lithium iron phosphate, ammonium molybdate and phosphoric acid in the manganese-doped lithium iron phosphate is 5: (0.12-0.2): (0.02-0.03), and in the exemplary embodiment, it can be a typical but non-limiting molar ratio of 5: 0.12: 0.02, 5: 0.2: 0.03, or a range between any two molar ratios. In this case, the ammonium molybdate is reacted completely.
[0075] The concentration of phosphoric acid can be adjusted as needed. However, as an example, the mass concentration of phosphoric acid can be 60% to 85%. In the exemplary embodiment, it can be 60%, 70%, 80%, 85% and other typical but non-limiting mass concentrations or a range between any two mass concentrations. The Keggin structure in the precursor prepared by phosphoric acid is stably modified manganese-doped lithium iron phosphate.
[0076] [Step S20]
[0077] In some embodiments, in the above step S20, the drying temperature is 100°C to 150°C, and the drying time is 0.5h to 3h; in an exemplary embodiment, the drying temperature can be 100°C, 120°C, 140°C, 150°C, etc., typical but non-limiting temperatures or a range between any two temperatures, and the drying time can be 0.5h, 2h, 3h, etc., typical but non-limiting times or a range between any two times. At this drying temperature and time, the solvent in the precursor is removed.
[0078] In some embodiments, in the above step S20, the dried product is washed with pure water for at least 2 times, and the volume of a single wash is at least 2 times the volume of the product. In this case, the pure water can remove impurities such as excess phosphoric acid and ammonium phosphate contained in the dried product.
[0079] In some embodiments, in the above step S20, spray drying includes pressure spray drying.
[0080] In some embodiments, the air inlet temperature in the pressure spray drying is 200°C to 300°C, the air outlet temperature is 95°C to 100°C, and the air inlet pressure is 0.2MPa to 0.6MPa. In the exemplary embodiment, the air inlet temperature of the spray drying can be a typical but non-limiting temperature such as 200°C, 250°C, 300°C, or a range between any two temperatures, and the air inlet pressure can be a typical but non-limiting time such as 0.2MPa, 0.4MPa, 0.6MPa, or a range between any two pressures. Under this spray granulation temperature and pressure, not only the Keggin structure in the prepared positive electrode active material will not be destroyed, but also the contact interface between manganese-doped lithium iron phosphate and ammonium phosphomolybdate can be stabilized, thereby improving the conductivity and conductivity rate of the positive electrode active material; in addition, the stable contact interface further stabilizes the Keggin structure, so that it will not be destroyed again under the high temperature environment of the subsequent carbon coating step.
[0081] In some specific embodiments, the high pressure gas in the spray drying is compressed air or an inert gas. In this case, the air or the inert gas does not chemically react with the material, and therefore does not generate new impurities.
[0082] In some specific embodiments, the inert gas is at least one of nitrogen, helium, neon, and argon.
[0083] In some specific embodiments, in the above step S20, the average particle size Dv50 of the product obtained by spray drying is 1 μm to 15 μm, and in the exemplary embodiment, it can be a typical but non-limiting average particle size such as 1 μm, 2 μm, 6 μm, 8 μm, 15 μm, or a range between any two average particle sizes. In this case, the particle size range can make the surface of the particles evenly coated with a carbon coating layer, thereby improving the conductivity of the material.
[0084] In some embodiments, in the above step S20, the manganese-doped lithium iron phosphate modified by ammonium phosphomolybdate is carbon-coated by chemical vapor deposition. It should be noted that the coating conditions such as gas and temperature of the chemical vapor deposition method can be adjusted according to actual conditions and are not limited. In the embodiment, the deposition temperature of the chemical vapor deposition method is 600°C~1000°C, which can be a typical but non-restrictive temperature such as 600°C, 650°C, 800°C, 850°C, 900°C, 1000°C, or a range between any two temperatures. In the embodiment, the carbon source of the chemical vapor deposition method includes but is not limited to one or more of methane, ethane, ethylene, and acetylene.
[0085] In other embodiments, in the above step S20, the manganese-doped lithium iron phosphate modified with ammonium phosphomolybdate is carbon-coated by a sintering method. It should be noted that the coating conditions of the sintering method can also be adjusted according to actual conditions and are not limited. As an example, the step of carbon coating by the sintering method includes: heat preservation under an inert atmosphere and specific temperature conditions, wherein the inert gas can be nitrogen, argon, etc., the specific temperature is 450°C~800°C, and the insulation time is 3h~9h. As an example, the carbon source required for the sintering method can be one or any combination of glucose, polyethylene glycol, citric acid, and sucrose.
[0086]
Positive electrode
[0087] A third aspect of the embodiments of the present application provides a positive electrode plate, which includes the positive electrode active material of the embodiments of the present application or the positive electrode active material prepared by the preparation method of the embodiments of the present application.
[0088] In some embodiments, the positive electrode sheet includes a current collector and a positive electrode film layer disposed on at least one surface of the current collector;
[0089] The positive electrode film layer contains the positive electrode active material of the embodiment of the present application or the positive electrode active material prepared by the preparation method of the embodiment of the present application.
[0090] In the above-mentioned “at least one surface of the current collector”, the surface refers to the surface of the current collector perpendicular to the thickness direction of the current collector.
[0091] Exemplarily, the thickness of the positive electrode plate is 0.15 mm to 10 mm; this thickness is only exemplary, and the thickness can be adjusted according to actual needs and is not limited to this thickness range.
[0092] In some embodiments, the current collector material includes one or more of a carbon material, a metal material, and a carbon fiber composite material.
[0093] In some embodiments, the carbon material includes one or more of natural graphite, artificial graphite, carbon black, and carbon fiber.
[0094] In some embodiments, the metal material includes one or more of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, silver alloy, copper, and copper alloy.
[0095] In some embodiments, the positive electrode film layer contains the positive electrode active material of the embodiment of the present application or the positive electrode active material prepared by the preparation method of the embodiment of the present application.
[0096] In some embodiments, the method for preparing a positive electrode film layer comprises:
[0097] The positive electrode slurry is coated on the current collector, and a positive electrode film layer is obtained through steps including drying and cold pressing;
[0098] The positive electrode slurry includes positive electrode active materials.
[0099] Exemplarily, the thickness of the positive electrode film layer is 0.1 mm to 8 mm; this thickness is only exemplary, and the thickness can be adjusted according to actual needs and is not limited to this thickness range.
[0100]
Battery
[0101] A fourth aspect of the present application provides a battery, including a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte;
[0102] The positive electrode plate includes the positive electrode plate of the embodiment of the present application.
[0103] The battery of the embodiment of the present application has excellent conductivity, cycle stability and rate performance because the positive electrode uses a positive electrode plate containing the positive electrode active material of the embodiment of the present application or the positive electrode active material prepared by the preparation method of the embodiment of the present application, thereby making the positive electrode of the battery have excellent conductivity, cycle stability and rate performance.
[0104] In some embodiments, the isolation membrane includes one or more of a porous polymer membrane, a non-woven fabric membrane, and an inorganic composite membrane.
[0105] In some embodiments, the material of the porous polymer membrane includes polyethylene (PE) and / or polypropylene (PP).
[0106] In some embodiments, the material of the non-woven fabric separator includes one or more of polyimide (PI), polyester (such as polyethylene terephthalate PET), cellulose, polyamide (PA), and aramid.
[0107] In some embodiments, the nonwoven membrane is a nanofiber nonwoven membrane, including a polyimide nanofiber membrane. In this case, the nanofiber nonwoven membrane has a higher specific surface area and stronger adsorption capacity, and can more effectively isolate the positive and negative electrodes and promote the transmission of lithium ions.
[0108] In some embodiments, the non-woven fabric separator is a ceramic-coated non-woven fabric separator, that is, a ceramic powder (such as Al2O3, SiO2, etc.) is coated on the surface of the non-woven fabric separator (thickness 2μm~15μm). This ceramic-coated non-woven fabric separator not only inherits the high porosity and air permeability of the non-woven fabric, but also increases its thermal stability and mechanical strength.
[0109] In some embodiments, the inorganic composite membrane includes a ceramic-coated composite membrane and an inorganic-organic composite membrane;
[0110] Among them, the ceramic-coated composite membrane is a polymer membrane (such as polyethylene PE, polypropylene PP, etc.) coated with one or more layers of ceramic coating; the ceramic coating can significantly improve the thermal stability and chemical stability of the membrane while maintaining the flexibility and mechanical strength of the polymer membrane;
[0111] Inorganic-organic composite membranes are made by combining inorganic materials with polymer materials through blending, copolymerization or lamination. This composite membrane combines the advantages of inorganic materials and polymer materials and has higher comprehensive performance.
[0112] In some embodiments, the isolation film has a thickness of 60 μm to 100 μm.
[0113] In some embodiments, the negative electrode plate is a common battery plate, generally including a current collector and a negative electrode film layer; the negative electrode film layer contains a negative electrode active material, and the specific negative electrode material and content can be selected according to actual needs without limitation. The preparation of the negative electrode film layer is basically the same as that of the positive electrode film layer.
[0114] In some embodiments, the electrolyte includes an electrolyte salt and a solvent. The materials and contents of the electrolyte salt and the solvent are selected according to actual needs and are not limited.
[0115] The following describes the invention in conjunction with specific embodiments.
[0116] Example 1
[0117] Example 1 provides a method for preparing a positive electrode active material, comprising the following steps:
[0118] (1) A 20% by mass ammonium molybdate solution was prepared with a molar ratio of manganese-doped lithium iron phosphate to ammonium molybdate of 5:0.12 and water as a solvent, and then 0.1% by mass of hexadecyltrimethylammonium bromide of the mass of lithium iron phosphate was added, and the manganese-doped lithium iron phosphate was dispersed in the ammonium molybdate solution under stirring to obtain a mixed suspension.
[0119] (2) At a temperature of 80° C., adding a phosphoric acid solution with a mass concentration of 85% to the mixed suspension, stirring at 180 rpm for reaction for 3 hours to obtain a reaction solution; wherein the components in the mixed suspension include manganese-doped lithium iron phosphate and ammonium molybdate, the molar ratio of manganese to lithium iron phosphate in the manganese-doped lithium iron phosphate is 0.05:1; the molar ratio of lithium iron phosphate, ammonium molybdate and phosphoric acid in the manganese-doped lithium iron phosphate is 5:0.12:0.03.
[0120] (3) The pH value of the reaction solution is adjusted with concentrated ammonia water to obtain a precursor with a pH value of 4.
[0121] (4) Dry the precursor at 120°C for 2 h; wash it twice with pure water, and then spray granulate it under hot air at 350°C for 5 min.
[0122] (5) Using acetylene as a carbon source, a carbon coating layer with a thickness of 15 nm is coated on the surface of the spray granulated product by chemical vapor deposition, wherein the deposition temperature is 650°C, to obtain a positive electrode active material.
[0123] Example 1 also provides a positive electrode active material, which is prepared using the preparation method of this example.
[0124] The tap density of the positive electrode active material is 1.5 g / cm 3 .
[0125] Example 2
[0126] Example 2 proposes a positive electrode active material and a preparation method. The material and the preparation steps are basically the same as those in Example 1, except that in the preparation method, the pH value of the precursor is 3.
[0127] The tap density of the positive electrode active material is 1.35 g / cm 3 .
[0128] Example 3
[0129] Example 3 proposes a positive electrode active material and a preparation method. The material and the preparation steps are basically the same as those in Example 1, except that in the preparation method, the pH value of the precursor is 5.
[0130] The tap density of the positive electrode active material is 1.32 g / cm 3 .
[0131] Example 4
[0132] Example 4 proposes a positive electrode active material and a preparation method. The material and the preparation steps are basically the same as those in Example 1, except that in the preparation method, the molar ratio of lithium iron phosphate, ammonium molybdate and phosphoric acid in manganese-doped lithium iron phosphate is 5:0.2:0.028.
[0133] The tap density of the positive electrode active material is 1.45 g / cm 3 .
[0134] Example 5
[0135] Example 5 proposes a positive electrode active material and a preparation method. The material and its preparation steps are basically the same as those in Example 1, except that: in the preparation method, the molar ratio of lithium iron phosphate, ammonium molybdate and phosphoric acid in manganese-doped lithium iron phosphate is 5:0.16:0.025; and the pH value of the reaction solution is adjusted to 4 using dilute nitric acid with a concentration of 10%.
[0136] The tap density of the positive electrode active material is 1.39 g / cm 3 .
[0137] Example 6
[0138] Example 6 proposes a positive electrode active material and a preparation method. The material and its preparation steps are basically the same as those in Example 1, except that: in the preparation method, the molar ratio of lithium iron phosphate, ammonium molybdate and phosphoric acid in manganese-doped lithium iron phosphate is 5:0.17:0.029; and the pH value of the reaction solution is adjusted to 4 using dilute nitric acid with a concentration of 10%.
[0139] The tap density of the positive electrode active material is 1.37 g / cm 3 .
[0140] Example 7
[0141] Example 7 proposes a positive electrode active material and a preparation method. The material and its preparation steps are basically the same as those in Example 1, except that: in the preparation method, the molar ratio of lithium iron phosphate, ammonium molybdate and phosphoric acid in manganese-doped lithium iron phosphate is 5:0.15:0.03; and the pH value of the reaction solution is adjusted to 4 using dilute nitric acid with a concentration of 10%.
[0142] The tap density of the positive electrode active material is 1.48 g / cm 3 .
[0143] Comparative Example 1
[0144] Comparative Example 1 proposes a method for preparing a positive electrode active material, and the steps are basically the same as those of Example 1, except that the pH value of the precursor is 8.
[0145] Comparative Example 1 also proposes a positive electrode active material, which is prepared by the preparation method of this comparative example. The tap density of the positive electrode active material is 0.51 g / cm 3 .
[0146] Comparative Example 2
[0147] Comparative Example 2 proposes a method for preparing a positive electrode active material, and the steps are basically the same as those of Example 1, except that the pH value of the precursor is 1.
[0148] Comparative Example 2 also proposes a positive electrode active material, which is prepared by the preparation method of this comparative example. The tap density of the positive electrode active material is 0.67 g / cm 3 .
[0149] Comparative Example 3
[0150] Comparative Example 3 proposes a method for preparing a positive electrode active material, and the steps are basically the same as those of Example 1, except that in the preparation method, the molar ratio of lithium iron phosphate, ammonium molybdate and phosphoric acid in manganese-doped lithium iron phosphate is 5:0.12:0.05.
[0151] Comparative Example 3 also proposes a positive electrode active material, which is prepared by the preparation method of this comparative example. The tap density of the positive electrode active material is 0.53 g / cm 3 .
[0152] In order to verify the advancement of the positive electrode active material and the preparation method thereof proposed in the examples of the present application, firstly, taking Example 1 as an example, a scanning electron microscope was used to scan the positive electrode active material prepared in Example 1, and the corresponding Figure 2 The SEM image shown; the positive electrode active materials prepared in the embodiment and the comparative example are then made into button batteries, and the preparation steps are as follows:
[0153] (1) Preparation of positive electrode slurry: positive electrode active material: carbon nanotube: polyvinylidene fluoride were mixed in a mass ratio of 90:5:5, and solvent N-methylpyrrolidone (NMP) was added to adjust the viscosity to 4000 mPa·s~8000 mPa·s to prepare positive electrode slurry.
[0154] (2) The positive electrode slurry is evenly coated on one surface (perpendicular to the thickness direction) of the aluminum foil (positive electrode current collector) and dried, and then rolled and sliced to obtain a positive electrode sheet containing a positive electrode film layer.
[0155] (5) Using lithium hexafluorophosphate-ethyl methyl carbonate as the electrolyte and polypropylene as the isolation membrane, the prepared positive electrode sheet and negative lithium sheet are combined to make a button half-cell.
[0156] The button cells were tested for electrical properties in the voltage range of 2.0V to 3.8V using Blue Electric equipment, including 0.1C discharge, 0.1C first charge and discharge efficiency, 5C discharge, and 1C cycle 500 capacity retention rate. The test results are shown in Table 1 below.
[0157]
[0158] From the above table 1 and Figure 2 At least the following conclusions can be drawn:
[0159] 1) Combine Table 1 and Figure 2 It can be seen that the positive electrode active materials of ammonium phosphomolybdate-modified lithium iron phosphate and carbon-coated ammonium phosphomolybdate-modified lithium iron phosphate provided in the embodiments of the present application have very high rate performance, electrochemical performance and cycle stability.
[0160] 2) The pH value of the precursor has a great influence on the performance and stability of the positive electrode active material product. At a pH value of 3-5, the generated ammonium phosphomolybdate stably modifies the manganese-doped lithium iron phosphate, and combined with the carbon coating layer, the cycle stability of the prepared positive electrode active material is very high.
[0161] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A positive electrode active material, characterized in that: including ammonium phosphomolybdate, manganese-doped lithium iron phosphate and a carbon coating; The ammonium phosphomolybdate modified manganese doped lithium iron phosphate; The carbon coating layer coats ammonium phosphomolybdate-modified manganese-doped lithium iron phosphate.
2. The positive electrode active material according to claim 1, characterized in that In the manganese-doped lithium iron phosphate, the molar ratio of manganese to lithium iron phosphate is 0.005-0.05:
1.
3. The positive electrode active material according to claim 1, characterized in that The molar ratio of the lithium iron phosphate of the manganese-doped lithium iron phosphate to the ammonium phosphomolybdate is 5:0.01-0.
02.
4. The positive electrode active material according to claim 1, characterized in that The carbon coating layer is at least one layer, and the thickness of a single carbon coating layer is 10nm-30nm.
5. The positive electrode active material according to any one of claims 1 to 4, characterized in that: The tap density of the positive electrode active material is 0.7 g / cm 3 ~1.5g / cm 3 .
6. A method for preparing a positive electrode active material according to any one of claims 1 to 5, characterized in that: The steps include: Adding phosphoric acid solution to the mixed suspension for mixed reaction to obtain a precursor; wherein the components in the mixed suspension include manganese-doped lithium iron phosphate and ammonium molybdate; The precursor is dried, washed, spray-dried, and then carbon-coated to obtain a positive electrode active material.
7. The method for preparing a positive electrode active material according to claim 6, characterized in that: The preparation method steps satisfy at least one of the following 1) to 4): 1) The mixed reaction comprises the steps of: adding a phosphoric acid solution to a mixed suspension at a temperature of 60° C. to 90° C. and stirring for a reaction of 1 h to 3 h to obtain a reaction solution; adjusting the pH value of the reaction solution with a pH adjuster to obtain a precursor with a pH value of 3 to 5; 2) The molar ratio of lithium iron phosphate, the ammonium molybdate and the phosphoric acid in the manganese-doped lithium iron phosphate is 5:0.12-0.20:0.020-0.030; 3) The drying temperature is 100°C to 150°C and the drying time is 0.5h to 3h; 4) The spray drying includes pressure spray drying, in which the inlet air temperature is 200°C to 300°C, the outlet air temperature is 95°C to 100°C, and the inlet air pressure is 0.2MPa to 0.6MPa.
8. A positive electrode sheet, characterized in that: The positive electrode sheet includes the positive electrode active material according to any one of claims 1 to 5 or the positive electrode active material prepared by the preparation method according to any one of claims 6 to 7.
9. A battery comprising a positive electrode sheet, a separator, a negative electrode sheet and an electrolyte; characterized in that: The positive electrode sheet includes the positive electrode sheet according to claim 8.
10. Use of the positive electrode active material according to any one of claims 1 to 5, the positive electrode active material obtained by the preparation method of the positive electrode active material according to any one of claims 6 to 7, the positive electrode sheet according to claim 8 or the battery according to claim 9 in household appliances, electric vehicles, ships, satellites or energy storage systems.
Citation Information
Patent Citations
Modified lithium iron phosphate positive electrode material and preparation method thereof, positive plate and lithium secondary battery
CN109390563A
Positive electrode material of lithium ion battery and preparation method of positive electrode material
CN117219764A